The introduction of an annual pasture legume into a tree cropping system - Russi L.; Falcinelli M. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In Italy fields of vineyards and olive trees offer a potential to the introduction of an herbaceous crop into the tree system. This may have several advantages, but the presence of a canopy is particularly worth of interest in hilly lands where soils are prone to erosion. Here we suggest the use of annual pasture legumes. At this purpose 28 genotypes of Medicago polymorpha were evaluated in Perugia from 1995 to 1999 for soil cover, canopy growth, cold tolerance, biomass production, flowering time, seed yield, hardseededness and stand regeneration in autumn. Entries differed enormously for most of the characters considered, thus allowing a broad choice, depending on the need of the system.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)